Etiology of apneic episodes in infants aged <1 year and validation of brief resolved unexplained events risk-stratification criteria without age as a risk factor - Hellström Schmidt, Sanna; Sotoca Fernandez, Jorge; Pronk, Cornelis Jan; Orfanos, Ioannis (Frontiers in Pediatrics, 2026)
The criteria for Brief Resolved Unexplained Events (BRUE) are used to stratify the risk in infants presenting with apneic episodes. However, these criteria often classify a high proportion of infants as higher risk. This study aimed to investigate the etiology of apneic episodes, particularly those compatible with BRUE, and to assess whether age ≤60 days is associated with serious underlying conditions. We conducted a retrospective study of infants aged <1 year who presented with apnea as the chief complaint or had an ICD-10 code P28.4 (Other apnea of newborn) recorded between 2014 and 2018 at Skåne Pediatric University Hospital. The cohort was divided into a BRUE subgroup, which was further stratified into lower- and higher-risk groups based on current BRUE criteria, and additionally stratified without considering age as a higher-risk factor. Infants with an ICD diagnosis related to respiratory tract infection (RTI) or clinical signs of RTI were categorized into a separate RTI sub-cohort. A total of 340 infants were included. No specific diagnosis was identified in 253 (74.4%) cases, while 63 (18.5%) were diagnosed with viral RTIs. There were 9 (2.6%) cases with serious conditions during the first encounter, all of whom appeared unwell or had alarming signs at presentation excluding them from a BRUE diagnosis. The BRUE sub-cohort included 188 infants, of whom 143 (76.1%) were classified as higher risk using current criteria. When age ≤60 days was excluded as a risk factor, only 45 (23.9%) were classified as higher risk. None of the infants with serious diagnoses were misclassified as lower risk under the modified criteria. The RTI sub-cohort included 158 infants, with 111 (70.3%) hospitalized; 90 of these (81.1%) were discharged within two days. Serious underlying conditions and complicated clinical courses were rare among well-appearing infants aged under 1 year, with apneic episodes. Age ≤60 days did not appear to be associated with serious diagnoses in the BRUE sub-cohort. Well-appearing infants with RTI symptoms also had benign outcomes. These findings suggest that age may warrant re-evaluation as a risk factor in BRUE stratification, and that well-appearing infants with RTI symptoms may be appropriately classified as low risk.